Evolution of the high-end computing market in the USA. (1st January 2002) - Foster, Roger S.; Gupta, Amar; Deshpande, Sawan
This paper focuses on the technological change in the high-end computing market. The discussion combines historical analysis with strategic analysis to provide a framework to analyse a key component of the computer industry. This analysis begins from the perspective of government research and development spending; then examines the confusion around the evolution of the high-end computing market in the context of standard theories of technology strategy and new product innovation. Rather than the high-end market being "dead", one should view the market as changing due to increased capability and competition from the low-end personal computer market. The high-end market is also responding to new product innovation from the introduction of new parallel computing architectures. In the conclusion, key leverage points in the market are identified and the trends in high-end computing are highlighted with implications